How Green is Green Islam? Religious Environmentalism and Public Policy in Indonesia - Wijsen, Frans (Studia Islamika, 2025)
Studies of religious environmentalism often start from the assumption that religious communities are essential to the fight against environmental changes. In this article I will address the question whether and in what way this is indeed the case, and if and how religious environmental ethics can be integrated into public policy. Numerous large-scale studies show that evidence for a relationship between religious beliefs and environment-friendly behavior is not robust. Integrating religious beliefs into public policy is not unambiguous. This article has two parts. In the first part I draw on the religious environmentalism actions study and the humans and nature study to explore empirical evidence for a relationship between religious beliefs and environmental ethics in Indonesia. In the second part I ask what this evidence signifies for environmental policy making. I advocate a discursive approach in policy-making showing the multiplicity of meanings of environmental problems and the need of forming discourse coalitions.